Three-dimensionally rendering of the sphenoid bone of adolescents using Materialise’s Interactive Medical Image Control System software (Research, Society and Development, 2022)
The main goal of this study was to reconstruct three-dimensionally (3D) the sphenoid bone of adolescents with the software Materialise Mimics to test the accuracy and reliability of craniometric measurements performed with the software. The study was conducted according to Strengthening the Reporting of Observational studies in Epidemiology (STROBE) guidelines. Cone-Beam Computed Tomography (CBCT) was performed in adolescents before the orthodontic treatment as part of the orthodontic records. The CBCT images were exported as DICOM (Digital Imaging and Communication in Medicine) files, in a universal format, with a voxel size of 0.3 mm and sphenoid bone was three-dimensionally rendered with Software Materialise Mimics. Ten sphenoid measurements were performed in triplicate by two trained examiners. The studied population was composed of 26 adolescents, 16 females (61.5%), and 10 males (38.5%) with a mean age of 12.5 years (SD= 1.7). 60 measurements were taken and the intra and inter-examiner accuracy revealed a high degree of data reproducibility (Kappa test higher than 0.90). The reconstruction and rendering of the images obtained by CBTC allowed anatomical details of the sphenoid bone to be measured with very high reproducibility.  The Software Materialise Mimics allows you to analyze anatomical structures in detail and presents useful tools to optimize craniometry analyses.